Performance management of SMEs: a systematic literature review for antecedents and moderators. Issue 1 (26th November 2020) - Kafetzopoulos, Dimitrios
Abstract : Purpose: The purpose of this study is to gain insight into existing empirical studies on performance management of small and medium-sized enterprises (SMEs). It categorizes the main antecedents for SMEs' performance, the dimensions of SMEs' performance and all variables used as moderators in the conceptual relationships. Design/methodology/approach: This study undertakes a systematic literature review of 58 articles published in 33 peer-reviewed academic journals from 2000 to 2020 followed by a synthesis of individual studies to analyze the trends and background of research into SMEs. Findings: A new academic conceptual model was developed grounded in selected theoretical lenses to advance our understanding of the different categories of antecedents, moderators and SMEs' performance dimensions. Research limitations/implications: The author has provided a future research agenda in the context of SMEs. Future studies may investigate the role of different categories of determinants, the influence of key cultural values, the digital capability in SMEs and the Internet in the internationalization of SMEs. Practical implications: This paper offers a framework for both practitioners and scholars in thinking about those factors that may be critical for success in SMEs. Originality/value: This is a systematic review that suggests a new conceptual model of what existing empirical studies have found on SMEs. It can be used to influence thinking and research design in the area of SMEs' performance and success.